Tourism Competitiveness Archetypes and the Frontier Distance Gaps of Uzbekistan - Sobirov Bobur (Universitas Muhammadiyah Sidoarjo, 2025)
This study analyzes the tourism competitiveness archetypes and frontier destination gaps of Uzbekistan alongside ten leading tourism economies using metrics from the 2024 Travel and Tourism Development Index. By applying unsupervised principal component analysis and k-means clustering, this research reveals a distinct three-tier structure where advanced economies split into two high-performance variants, while Uzbekistan forms an isolated third cluster. The analysis shows that the primary principal component explains 84% of total profile variance, illustrating that the emerging destination faces a broad-based, structural deficit across all evaluation pillars rather than a localized weakness. This study provides recommendations for national policy architectures to move away from isolated single-pillar interventions and instead deploy integrated, multi-dimensional strategies that target balanced long-term upgrading across environmental sustainability, infrastructure, safety, and health frameworks. Highlights: - Three-Tier Competitiveness Archetypes – Advanced economies split into two high-performance variants, while Uzbekistan forms an isolated third cluster. - Structural Profile Deficit – Principal component analysis captures 84% of total variance, revealing broad-based weaknesses across all evaluation pillars. - Integrated Policy Upgrading – Recommendations focus on shifting away from isolated interventions toward multi-dimensional strategies across health and sustainability frameworks. Keywords: Tourism Competitiveness, Cluster Analysis, Principal Components, Archetypes, Destination Benchmarking.